People's Republic of China-Hong Kong Special Administrative Region : 2016 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that with a soft global trade environment and a downturn in tourism arrivals from Mainland China, the growth rate of Hong Kong Special Administrative Region is expected to have slowed to 1.5 percent in 2016. Growth is likely to pick up modestly to about 2 percent in 2017, with private consumption continuing to be a main driver supported by a steady labor market. The current account surplus remained below 3 percent of GDP. Over the longer term, aging pressures may weaken the structural fiscal position, requiring fiscal planning to alleviate the decline, and a housing supply shortage also needs to be tackled.